An experimental comparison of the Marcus-Hush and Butler-Volmer descriptions of electrode kinetics applied to cyclic voltammetry. The one electron reductions of europium (III) and 2-methyl-2-nitropropane studied at a mercury microhemisphere electrode - Henstridge, M; Wang, Y; Limon-Petersen, J; Laborda, E; Compton, R (2011)
We present a comparative experimental evaluation of the Butler-Volmer and Marcus-Hush models using cyclic voltammetry at a microelectrode. Numerical simulations are used to fit experimental voltammetry of the one electron reductions of europium (III) and 2-methyl-2-nitropropane, in water and acetonitrile, respectively, at a mercury microhemisphere electrode. For Eu (III) very accurate fits to experiment were obtained over a wide range of scan rates using Butler-Volmer kinetics, whereas the Marcus-Hush model was less accurate. The reduction of 2-methyl-2-nitropropane was well simulated by both models, however Marcus-Hush required a reorganisation energy lower than expected. © 2011 Elsevier B.V. All rights reserved.